Kalibrasi Simulasi Breakwater Di Pantai Bantan Kab. Bengkalis - Doli Ananta Putra; Bambang Sujatmoko; Manyuk Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Bantan Coast in Bengkalis Island that suffered worst abrasion due to wave attack. Protection of abrasion area against the wave can be done by proper lay-out of breakwater with certain configuration. To get the optimal configuration of breakwater, wave pattern around the breakwater were analyzed quantitatively. It was conducted to obtain the optimum condition of wave height reduction produced. Evaluation of breakwater lay-out effect to wave pattern can be done by numerical model approached. Wave pattern simulation that occurred due to the breakwater was done by Surface water Modelling System (SMS) - CGWAVE software module. This module is a 2-D depth average numerical model using finite element model. To get accurate simulation, a deviation of the numerical result and the measurement result at several locations was used as the indicator parameter in the calibration process. Based on the forecasting of the empirical wave method, the period of 5.4 seconds; 1.30 meters high as data input. Calibration Results of numerical models of semicircular radius (R = 2000m) in modeling to achieve wave height (H = 1.1m). Keywords : Bantan Coast, breakwater simulation, SMS-CGWAVE